36th AIAA/ASME/SAE/ASEE Joint Propulsion Conference and Exhibit 2000
DOI: 10.2514/6.2000-3421
|View full text |Cite
|
Sign up to set email alerts
|

A study of cylindrical Hall thruster for low power space applications

Abstract: A 9 cm cylindrical thruster with a ceramic channel exhibited performance comparable to the state-of-the-art Hall thrusters at low and moderate power levels. Significantly, its operation is not accompanied by large amplitude discharge low frequency oscillations. Preliminary experiments on a 2 cm cylindrical thruster suggest the possibility of a high performance micro Hall thruster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Raitses et al [16] developed a cylindrical Hall thruster (CHT), combining the conventional annular design with the simplicity and enhanced volume-to-surface-area ratio of the end-Hall thruster (EHT). The CHT channel features an annular region near the anode, followed by a cylindrical region.…”
mentioning
confidence: 99%
“…Raitses et al [16] developed a cylindrical Hall thruster (CHT), combining the conventional annular design with the simplicity and enhanced volume-to-surface-area ratio of the end-Hall thruster (EHT). The CHT channel features an annular region near the anode, followed by a cylindrical region.…”
mentioning
confidence: 99%
“…It is important to note that Hall thrusters operating at power levels below 500 W are currently not available but are in the research phase of development (c.f. [10,11]…”
Section: Discussionmentioning
confidence: 99%
“…These findings have shown that the spectral response of the plasma depends on the position inside the thruster, ion mass and density, ion-accelerating discharge voltage, channel geometry, and the magnetic field gradient and magnitude. All of this prior thruster research in the realm of plasma-thruster instabilities has focused on the relationship of these modes to various discharge settings [7][8][9][10][11][12][13][14][15] and thruster geometries [16][17] . While the use of active feedback control for mitigating these instabilities has been suggested in the past 9,10 , there has yet to be an actively controlled Hall thruster in closed loop at frequencies near the dominant breathing mode.…”
Section: B Plasma Instabilities and Oscillatory Modesmentioning
confidence: 99%